Perancangan dan Pembuatan Ragum Kerja Kayu - Budriyadi, Syefi; A.L. Andriana Syarip; Maryoni; Mulyadi (Universitas Nusa Putra, 2021)
Woodworking vise is one of the tools to support the work process or practice at an institute that can be found on a daily basis. In general, the vise is made of castings. Seeing that to make the process of making vise easier, especially wooden vise using raw materials from 15 mm thick plate and iron. So based on the analysis of the problems above, the author tries to make a wooden work vise to meet these needs. This vise propulsion is planned to still use a manual process that is adjusted to the needs of consumers. The result of this final project is to produce a design and working drawing of a modification of a wooden vise. The resulting vise has a strong and anti-rust construction and has a diameter of ± length x width x height 442x 248 x 124 mm. Previously it was necessary to plan, design and manufacture appropriate vise components, easy to obtain, inexpensive and in accordance with the needs of craftsmen. This tool may be difficult to find in the market. The design system used is the VDI 2221 method, created by Gerhardt Pahl and Wolfgang Beits with the title